Electrocorticography to Investigate Age-Related Brain Lateralization on Pediatric Motor Inhibition - Kuo, Chao-Hung; Casimo, Kaitlyn; Wu, Jing; Collins, Kelly; Rice, Patrick; Chen, Bo-Wei; Yang, Shih-Hung; Lo, Yu-Chun; Novotny, Edward J.; Weaver, Kurt E.; Chen, You-Yin; Ojemann, Jeffrey G. (Frontiers in Neurology, 2022)
Response inhibition refers to the ability to suppress inappropriate actions that interfere with goal-driven behavior. The inferior frontal gyrus (IFG) is known to be associated with inhibition of a motor response by assuming executive control over motor cortex outputs. This study aimed to evaluate the pediatric development of response inhibition through subdural electrocorticography (ECoG) recording. Subdural ECoG recorded neural activities simultaneously during a Go/No-Go task, which was optimized for children. Different frequency power (theta: 4–8 Hz; beta: 12–40 Hz; high-gamma (HG): 70–200 Hz) was estimated within the IFG and motor cortex. Age-related analysis was computed by each bandpass power ratio between Go and No-Go conditions, and phase-amplitude coupling (PAC) over IFG by using the modulating index metric in two conditions. For all eight pediatric patients, HG power was more activated in No-Go trials than in Go trials, in either right- or left-side IFG when available. In the IFG region, the power over theta and HG in No-Go conditions were higher than those in Go conditions, with significance over the right side (p < 0.05). The age-related lateralization from both sides to the right side was observed from the ratio of HG power and PAC value between the No-Go and Go trials. In the pediatric population, the role of motor inhibition was observed in both IFG, with age-related lateralization to the right side, which was proved in the previous functional magnetic resonance imaging studies. In thus study, the evidence correlation of age and response inhibition was observed directly by the evidence of cortical recordings.